Improving Learning Outcomes of Islamic Education and Ethics with Audiovisual Supported Demonstration Methods in Extraordinary Schools - Ujang Prayitno (FITK UIN Walisongo Semarang, 2024)
This action research focuses on efforts to improve learning outcomes in Islamic Religious Education (PAI) subjects at Sekolah Luar Biasa (SLB) Negeri Tanggamus, especially for grade I students with special needs. Initial results show that only 20% of students understand the subject matter. This is due to the use of lecture methods without media support that is less effective. Therefore, this study aims to improve learning methods by using a mixed approach, especially through the application of demonstration methods supported by audiovisual media. This method is designed to create a more interactive and engaging learning environment, so that students can more easily understand the material presented. This research was conducted in four cycles, where each cycle showed a significant improvement in student learning outcomes. At the end of the study, the learning completeness reached 89.5%, far exceeding the initial target. These results show that the use of the demonstration method with audiovisual support is proven to be effective in increasing students' understanding of PAI material while strengthening character education. This research provides practical implications for the development of more innovative teaching strategies in religious education, especially for students with special needs, to ensure they can learn better and more enjoyably.